THE ROLE OF EXTRACURRICULAR SCOUTING ACTIVITIES IN FORMING CIVIC SKILLS IN STUDENTS - Billy Awaludin Ratu Dewan; Fitri Silvia Sofyan; Lusiana Rahmatiani (Journal Civics And Social Studies, 2026)
This study aims to describe the role of the Scouting extracurricular activity in developing civic skills in students at SMP IT ISP Karawang. The study used a descriptive qualitative method involving six subjects: the Vice Principal for Student Affairs, the Scouting extracurricular instructor, and three Scouting extracurricular members. Data collection techniques included in-depth interviews, participant observation, and documentation. Data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that the Scouting extracurricular activity has a strategic role in developing students' civic skills, including the ability to actively participate in social activities, effective communication skills, leadership, teamwork, discipline, and problem-solving. Routine, structured scouting activities based on the Dasa Dharma principles serve as a practical means of learning civic values. The instructor plays an important role in providing guidance, motivation, and role models that encourage active student involvement. School support and student enthusiasm also strengthen the achievement of these civic skills. These findings confirm that Scouting extracurricular activities not only support character development, but also serve as an effective vehicle for strengthening citizenship education in schools, particularly in the aspects of participatory skills and social responsibility.